Atraumatic Splenic Rupture in a Patient on Apixaban and Dual Antiplatelet Therapy. (June 2021) - Natarajan, Piruthiviraj; Thangarasu, Sudhagar; Ruck, Lela; Estrada, Paul; Gajendran, Mahesh; Renganathan, Gowri; Prakash, Bharat Ved; Aduroja, Olufemi
Splenic rupture due to any cause is a life-threatening complication and commonly attributed to trauma. Atraumatic splenic rupture is very rarely reported, and the incidence is currently unknown. Anticoagulants and dual anti-platelet medication can increase the chances of a splenic rupture. Surgical removal of the spleen may be warranted to prevent a life-threatening bleeding. Early identification and intervention are required for most patients as only a few qualify for medical management.